Relationship of maternal serum zinc level with gestational diabetes mellitus - Tamanna, Tabassum; Mahmood, Sharmeen; Nasrin, Begum; Das, Tripti Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Gestational diabetes mellitus (GDM) is a prevalent pregnancy disease in Bangladesh that poses risks to the health of both mother and fetus. Glycosuria-related nutritional deficiencies are often associated with GDM. Zinc, an essential micronutrient, plays a central role in insulin-mediated glucose metabolism and storage. Because of its importance in insulin-related processes, zinc deficiency is potentially relevant to pregnancy-related carbohydrate intolerance. The aim of this study was to evaluate the relationship of maternal zinc deficiency with gestational diabetes mellitus. Methods: This case-control study, conducted from October 2020 to September 2022, involved 160 pregnant women aged 18-35 from the Department of Obstetrics and Gynecology, BSMMU, Dhaka. Of these, 80 women diagnosed with GDM (24-40 weeks gestation) and 80 matched healthy controls were included in our study. Results: The mean (SD) zinc level was much lower in the cases than in the controls (59.60±19.37 µg/dl and 91.84±38.19 µg/dl, respectively; p-value = <0.001). There was a significant negative correlation of serum zinc levels with both FBG (r=-0.406, p<0.001) and 2HABG (r=-0.381, p<0.001). The likelihood of developing gestational diabetes was approximately 4.2 times higher in mothers with low serum zinc (<68 g/dL) than in mothers with zinc levels of 68 g/dL (p<0.001; OR=4.214; 95%- CI=2.158-8.231). Conclusions: Low maternal serum zinc levels have been found to be associated with gestational diabetes mellitus. Therefore, the serum zinc level can be used as a predictor to determine the risk of developing gestational diabetes mellitus.